Maximum extent of Late Pleistocene glaciers and last deglaciation of La Cerdanya mountains, Southeastern Pyrenees - Palacios, David (2015)
This paper examines glacial evolution in the La Pera and Malniu cirques, and Arànser, La Llosa and Duran valleys, in the Cerdanyamassifs on the south-facing slopes of the eastern Pyrenees. A geomorphologic analysis and dating of moraine boulders, glacially polished bedrock and rock glacier blockswere carried out by means of cosmogenic 36Cl surface exposure dating. The maximum ice advance was contemporary with the Last Glacial Maximum at 23 ka ago, and itwas of greater or only slightly lesser magnitude than for previous Quaternary advances. The termini of glaciers remained close to maximum positions, with minor advances and retreats until 18–17 ka when the glacial tongues disappeared from the valleys. Depending on the previous topography, these glaciers left behind a single polygenic moraine, in the case of confined valleys, or multiple moraines next to each other in the case of flat, more open areas. A final glacial advance is detected during the Oldest Dryas close to the cirque headwalls, and the glaciers finally disappeared during the Bølling interstadial. The glaciers were then replaced by rock glaciers, whose front immediately became inactive, although their activity continued near their source area until the early Holocene.